2004
DOI: 10.1079/phn2004648
|View full text |Cite
|
Sign up to set email alerts
|

Food store access and household fruit and vegetable use among participants in the US Food Stamp Program

Abstract: Objective: Recent research on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
371
4
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 505 publications
(394 citation statements)
references
References 9 publications
(15 reference statements)
12
371
4
7
Order By: Relevance
“…10 A number of studies have found correlations between the food environment and dietary intake. [30][31][32][33][34] One study in particular, using an experimental design, found that individuals who previously consumed few fruits and vegetables significantly increased their consumption after a new supermarket was built in their neighborhood. 35 These studies underscore the possibility that the association between supermarket access and obesity found in our analysis, as well as in earlier studies, may be predominately mediated by dietary consumption.…”
Section: Discussionmentioning
confidence: 99%
“…10 A number of studies have found correlations between the food environment and dietary intake. [30][31][32][33][34] One study in particular, using an experimental design, found that individuals who previously consumed few fruits and vegetables significantly increased their consumption after a new supermarket was built in their neighborhood. 35 These studies underscore the possibility that the association between supermarket access and obesity found in our analysis, as well as in earlier studies, may be predominately mediated by dietary consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread recognition of the relationship between the built environment, health status and food choices has led to growing interest in measuring aspects of the food store environment (8)(9)(10)(11)(12)(13)(14)(15) . However, few studies have examined both subjective (16,17) and objective measures of the food store environment and their association with weight and diet quality (7,(17)(18)(19)(20)(21)(22) . Perceived and objective measures each provide unique data that, taken together, can elucidate important factors operating at both the individual and the neighbourhood level.…”
Section: Discussionmentioning
confidence: 99%
“…No supermarkets were located within the study tracts. To be comprehensive in our description of store access, it was necessary to include supermarkets beyond the tract borders, since previous research has indicated the importance of supermarkets for consumption [5][6][7]26 . The completeness of the OPH database was verified by driving around the study neighbourhoods and visually locating all of the food retailers.…”
Section: Household Demographicsmentioning
confidence: 99%
“…For example, Morland et al found that with each additional supermarket in a census tract, fruit and vegetable intake increased 5 . Rose and Richards showed that increased supermarket access was a positive predictor of fruit consumption among participants in the US Food Stamp Program 6 , while Laraia et al found that pregnant women living in closer proximity to a supermarket consumed higher-quality diets 7 .…”
mentioning
confidence: 99%